2015
DOI: 10.1182/blood-2015-03-630947
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of idelalisib plus rituximab in treatment-naïve older patients with chronic lymphocytic leukemia

Abstract: • In 64 older patients with untreated CLL or small lymphocytic leukemia, treatment with idelalisib plus rituximab was generally well tolerated.• The combination produced a very high response rate (97%), including 19% complete remission.Idelalisib is a first-in-class oral inhibitor of PI3Kd that has shown substantial activity in patients with relapsed/refractory chronic lymphocytic leukemia (CLL Progression-free survival was 83% at 36 months. The most frequent (>30%) adverse events (any grade) were diarrhea (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
210
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(215 citation statements)
references
References 35 publications
(41 reference statements)
5
210
0
Order By: Relevance
“…Rapamycin potently inhibits mTOR, and is FDA approved for its immunosuppressant properties, and more recently to treat lymphangioleiomyomatosis (LAM) (164,165). Other developed inhibitors currently in clinical trials include targeting of either specific class I PI3-kinase isoforms, or so-called 'pan-PI3K' inhibitors (166)(167)(168). Despite some preclinical promise, using PI3K-pathway drugs as a monotherapy often leads to acquired resistance (168)(169)(170).…”
Section: Development Of Ras Inhibitors and Current Anti-ras Modalitiesmentioning
confidence: 99%
“…Rapamycin potently inhibits mTOR, and is FDA approved for its immunosuppressant properties, and more recently to treat lymphangioleiomyomatosis (LAM) (164,165). Other developed inhibitors currently in clinical trials include targeting of either specific class I PI3-kinase isoforms, or so-called 'pan-PI3K' inhibitors (166)(167)(168). Despite some preclinical promise, using PI3K-pathway drugs as a monotherapy often leads to acquired resistance (168)(169)(170).…”
Section: Development Of Ras Inhibitors and Current Anti-ras Modalitiesmentioning
confidence: 99%
“…15,18 O'Brien et al presented the first clinical trial of idelalisib with rituximab for the initial therapy of CLL in patients with a median age of 71 years, 42% of whom had advanced-stage disease. 15 The overall The effectiveness of idelalisib is particularly striking in patients with high-risk cytogenetic abnormalities like 17p deletion and in older CLL patients in whom chemoimmunotherapy is apparently less well-tolerated. Among the highest-risk TP53-mutated patients (n= 9), the overall response rate is 100% and none have progressed, consistent with the known excellent activity of idelalisib in relapsed patients in this high risk group (Figure 2).…”
Section: Idelalisib In Chronic Lymphoid Leukemiamentioning
confidence: 99%
“…5,6,[8][9][10][11][12][13][14][15][16][17] Recently published mature results of the initial treatment of CLL with idelalisib plus rituximab demonstrated that the combination is extremely effective with manageable toxicity in older CLL patients. 15,18 O'Brien et al presented the first clinical trial of idelalisib with rituximab for the initial therapy of CLL in patients with a median age of 71 years, 42% of whom had advanced-stage disease. 15 The overall The effectiveness of idelalisib is particularly striking in patients with high-risk cytogenetic abnormalities like 17p deletion and in older CLL patients in whom chemoimmunotherapy is apparently less well-tolerated.…”
Section: Idelalisib In Chronic Lymphoid Leukemiamentioning
confidence: 99%
“…Grade 3-4 toxicities in the idelalisib and rituximab arm were neutropenia (34%), thrombocytopenia (10%), elevated transaminases (5%), diarrhea (4%), and pyrexia (3%). Other trials with idelalisib include-idelalisib and rituximab in frontline setting [100], with ofatumumab, bendamustine, and rituximab.…”
Section: Idelalisib (Previously Gs-1101 or Cal-101)-p110 Pi3kd Inhibitormentioning
confidence: 99%